Miniplate Versus Reconstruction Bar Fixation for Oncologic Mandibular Reconstruction with Free Fibula Flaps - Cohen, Zack; Graziano, Francis D.; Shamsunder, Meghana G.; Shahzad, Farooq; Boyle, Jay O.; Cohen, Marc A.; Matros, Evan; Nelson, Jonas A.; Allen, Robert J., Jr. (Journal of Reconstructive Microsurgery, 2023)
Background Fibula free flaps (FFF) are the gold standard tissue for the reconstruction of segmental mandibular defects. A comparison of miniplate (MP) and reconstruction bar (RB)-based fixation of FFFs has been previously described in a systematic review; however, long-term, single-center studies comparing the two plating methods are lacking. The authors aim to examine the complication profile between MPs and RBs at a single tertiary cancer center. We hypothesized that increased components and a lack of rigid fixation inherent to MPs would lead to higher rates of hardware exposure/failure.Methods A retrospective review was performed from a prospectively maintained database at Memorial Sloan Kettering Cancer Center. All patients who underwent FFF-based reconstruction of mandibular defects between 2015 and 2021 were included. Data on patient demographics, medical risk factors, operative indications, and chemoradiation were collected. The primary outcomes of interest were perioperative flap-related complications, long-term union rates, osteoradionecrosis (ORN), return to the operating room (OR), and hardware exposure/failure. Recipient site complications were further stratified into two groups: early (<90 days) and late (>90 days).Results In total, 96 patients met the inclusion criteria (RB = 63, MP = 33). Patients in both groups were similar with respect to age, presence of comorbidities, smoking history, and operative characteristics. The mean follow-up period was 17.24 months. In total, 60.6 and 54.0% of patients in the MP and RB cohorts received adjuvant radiation, respectively. There were no differences in rates of hardware failure overall; however, in patients with an initial complication after 90 days, MPs had significantly higher rates of hardware exposure (3 vs. 0, p = 0.046).Conclusion MPs were found to have a higher risk of exposed hardware in patients with a late initial recipient site complication. It is possible that improved fixation with highly adaptive RBs designed by computer-aided design/manufacturing technology explains these results. Future studies are needed to assess the effects of rigid mandibular fixation on patient-reported outcome measures in this unique population.
Keywords: reconstruction bar; miniplate; fibula free flap; mandibulectomy; mandible reconstruction